2002
DOI: 10.1128/jcm.40.9.3485-3488.2002
|View full text |Cite|
|
Sign up to set email alerts
|

Direct PCR Detection of Burkholderia cepacia Complex and Identification of Its Genomovars by Using Sputum as Source of DNA

Abstract: We developed a nested PCR assay that detects the recA gene of the Burkholderia cepacia complex in sputum. The product of the first PCR round is also used to identify the genomovar of the pathogen. The protocol achieves high sensitivity and specificity with simple interpretation of genomovar status.Burkholderia cepacia is a multiresistant and transmissible opportunistic pathogen that frequently impairs the clinical state of patients with cystic fibrosis (CF) (1,3,9,10 (5). To reduce the probability of BCC sprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…To check the accuracy of culture-based identification and to determine the genomovar status of the Bcc, extracted DNA from each isolate was subject to generic and genomovar-specific PCRs as described previously (Drevinek et al, 2002). All the isolates were assigned to B. cenocepacia, recA group IIIA.…”
Section: Methodsmentioning
confidence: 99%
“…To check the accuracy of culture-based identification and to determine the genomovar status of the Bcc, extracted DNA from each isolate was subject to generic and genomovar-specific PCRs as described previously (Drevinek et al, 2002). All the isolates were assigned to B. cenocepacia, recA group IIIA.…”
Section: Methodsmentioning
confidence: 99%
“…Identification of BCC isolates to the species level based on the results obtained by genotypic methods, such as restriction fragment length polymorphism analysis of the recA gene or 16S rRNA genes (17,18) and recA gene-based PCR (4), is mostly done with research tools provided in reference centers. Phenotypic testing is still frequently used in routine laboratories.…”
mentioning
confidence: 99%
“…For accomplishing a sensitivity of 1.2 x 10 1 to 1.3 x 10 2 cfu per gram of sputum, a semi-nested PCR is required, where consecutive genomovar identification must then be performed by direct sequencing, excluding RFLP analysis [5]. Drvinek et al reported a nested PCR method with a first round of recA PCR, followed by a genomovar-specific amplification step with a sensitivity of 10 3 cfu/ml [6]. FISH technique employed via a 16S rRNA probe was reported to have 4 x 10 5 cfu/ml detection sensitivity when applied directly on sputum samples, but genomovar identification was not possible [19].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that commercial systems lack sufficient sensitivity and specificity for accurate identification of bacteria belonging to BCC group [3,4]. Recently, PCR-based methods are emerging as useful diagnostic tools for rapid identification and typing of BCC, also enabling direct detection of bacterial DNA from patient's sputum [2,5,6]. The ability of these assays to detect BCC in sputum is dependent on both selected target sequence and efficiency of DNA extraction procedure.…”
Section: Introductionmentioning
confidence: 99%